2024
DOI: 10.3390/polym16040543
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Particleboard Made of Agroforestry Residues Bonded with Thermosetting Adhesive Derived from Waste Styrofoam

Tati Karliati,
Muhammad Adly Rahandi Lubis,
Rudi Dungani
et al.

Abstract: This paper investigated the upcycling process of thermoplastic waste polystyrene (WPS) into thermosetting particleboard adhesive using two cross-linkers, namely methylene diphenyl diisocyanate (MDI) and maleic anhydride (MA). The WPS was dissolved in an organic co-solvent. The weight ratio of WPS/co-solvent was 1:9, and 10% of cross-linkers based on the WPS solids content were added subsequently at 60 °C under continuous stirring for 30 min. The adhesive properties, cohesion strength, and thermo-mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…In contrast, the loss modulus of the wood–MF-0 adhesive was higher than that of wood–MF-1. The loss modulus of a wood–adhesive interphase pertains to the capacity of the interface between the wood and the adhesive to release energy when subjected to dynamic loading conditions [ 57 ]. Various factors, such as adhesive formulation, curing conditions, wood surface preparation, and unique wood features, affect the loss modulus of the wood–adhesive interphase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the loss modulus of the wood–MF-0 adhesive was higher than that of wood–MF-1. The loss modulus of a wood–adhesive interphase pertains to the capacity of the interface between the wood and the adhesive to release energy when subjected to dynamic loading conditions [ 57 ]. Various factors, such as adhesive formulation, curing conditions, wood surface preparation, and unique wood features, affect the loss modulus of the wood–adhesive interphase.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in line with the stiffness of wood-MF resin as a function of temperature (Figure 8b). Wood-MF-0 reached a maximum stiffness of 957 N/m at 123.0 • C, while the wood-MF-1 had a maximum stiffness of 2734 N/m at 110.5 • C. The stiffness of wood adhesives is crucial in determining the overall structural integrity and performance of bonded wood products [57]. This study showed that MF-1 had a greater stiffness and could produce a better performance in its bonded wood products compared to MF-0.…”
Section: Wood-adhesive Interphase Analysismentioning
confidence: 99%